PENURUNAN KONSENTRASI COD DAN FENOL AIR LUMPUR LAPINDO DENGAN METODE OKSIDASI FENTON DAN UV - Evy Hendriarianti (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2007)
This research was carried out to investigate the removal of COD and phenol sludge filtrate by Fenton oxidation and UV after the treatment of coagulation-flocculation-sedimentation. Variation of treatments included UV intensity, H2O2 and FeSO4 concentration, and illumination time was 3 hours. The results showed that 92,71 % of COD removal and 100% of phenol removal (undetectable phenol) occurred at 36 Watt of UV, 250 mg/L of H2O2 and at 36 Watt of UV, 500 mg/L of H2O2. While 84,24% of COD removal occurred at Fenton variation of 500 mg/L of H2O2 : 100 mg/L of FeSO4 and 72 watt of UV light. Phenol removal of 98,84 % occurred at Fenton variation of 500 mg/L of H2O2 : 100 mg/L of FeSO4. and 36 watt of UV light.